Towards a Low-Cost Solution to Learn Robot Manipulator Control - Handy Wicaksono; Handry Khoswanto; Petrus Santoso (International Journal of Industrial Research and Applied Engineering, 2020)
Learn a robot manipulator in university requires a physical robot so students can learn to program it straight away. However, it is expensive and not affordable by most universities in Indonesia. We turn to a ROS-based solution for an open source, free and advanced robotic software system. Using ROS and Gazebo simulator, we develop a low-cost solution where students can learn an advanced robot manipulator such as Baxter. We divide our labwork into five sections: controlling the arm w.r.t. joints position, controlling the arm based on its inverse kinematics, object detection by a camera attached in robot’s wrist, executing a simple plan: pick and place task, and enabling a robot to perform a tool-use task. By gradually increasing the complexities of the labwork material we expect students get a better understanding in controlling a robot manipulator. We provide an affordable solution for students to learn robot manipulator control.